Collaborative R&D and the national research joint venture database : a statistical analysis - Link, Albert N. (Emerald points., 2021)
In light of a history of legislative actions in the United States to encourage collaborative R&D, this book characterizes U.S. collaborative R&D through the eyes of the National Research Joint Venture Database. Facilitating a fresh statistical look at collaborative R&D as a purposive strategy in the light of existing public policies, this book also provides a critical evaluation of the effectiveness of those attendant policies. Through an original project-based micro database, the author reveals the patterns of competitive behavior associated with collaborative R&D. Accompanied by follow-up statistical and econometric analyses, readers are not only confronted with what might be the most complete picture of U.S. collaborative R&D to date, but they are also provided with key indications of the effectiveness of U.S. legislative actions which is set to inspire further collaborations in research.